Existence of Small Periodic Solutions of Nonlinear Systems of Ordinary Differential Equations - Terekhin, M. T. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We investigate the case where conditions for the existence of a nonzero periodic solution of a system of ordinary differential equations are determined by the properties of elements of the matrix of linear approximation and the properties of nonlinear terms.